Immune Markers and Inflammatory Cytokines in Granulomatous Lobular Mastitis: A Case-Control Study - Li J; Zeng Y; Wang M; Liu Y; Guo Y; Zhao W; Huang Q; Zhang D (Dove Medical Press, 2024)
Jifeng Li, Yifei Zeng, Mengjie Wang, Yongxin Liu, Yubo Guo, Wenjie Zhao, Qiao Huang, Dongxiao Zhang Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Dongxiao Zhang, Department of Galactophore Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, No. 23, Art Museum Back Street, Dongcheng District, Beijing, 100010, People's Republic of China, Tel +8617864190977, Email Tzdx_thinking@126.comPurpose: Granulomatous lobular mastitis (GLM) has seen a rising incidence, though its pathogenesis remains unclear, posing challenges for treatment and contributing to high recurrence rates with conventional therapies. While the role of inflammatory and immune factors in GLM has been recognized, a comprehensive clinical evaluation of these markers is still lacking. This study aims to identify potential diagnostic markers and therapeutic targets by comparing immune markers and cytokine levels in GLM patients and healthy controls.Methods: Conducted at Beijing Hospital of Traditional Chinese Medicine, Capital Medical University from July 2023 to May 2024, this study enrolled 30 GLM patients and 15 healthy female controls in a 2:1 ratio. Serum levels of immune markers and cytokines were analyzed to explore their potential association with GLM.Results: The study population comprised 30 GLM patients with a mean age of 33.40 ± 4.12 years and 15 healthy female controls with a mean age of 32.13 ± 6.19 years. Significantly elevated levels of C-reactive protein (CRP), Immunoglobulin A (IgA), Complement Component 3 (C3), Complement Component 4 (C4), Compliment Component 1q (C1q), Alpha1-antit-rypsin (AAT), α 1-acidglycoprotein (AGP), Anti-histone antibodies (Anti-HIS), Anti-Ro52 antibodies (Anti-Ro52), Anti-double stranded DNA antibodies (Anti-dsDNA), Interleukin-6 (IL-6), Interleukin-10 (IL-10), and Tumor Necrosis Factor-α (TNF-α) were observed in GLM patients compared to controls (all P < 0.05). Subgroup analysis revealed higher levels of CRP, C3, C1q, AAT, and AGP in patients with larger mass areas and those with erythema nodosum (all P < 0.05). No significant differences were found in subgroups based on disease duration or recurrence (both P > 0.05).Conclusion: Serum levels of CRP, IgA, AAT, AGP, Anti-HIS, Anti-Ro52, Anti-dsDNA, C3, C4, C1q, IL-6, IL-10, and TNF-α may serve as diagnostic and prognostic indicators for GLM, with CRP, AAT, AGP, and C1q being particularly indicative of disease severity. These markers offer potential therapeutic targets for GLM.Keywords: granulomatous lobular mastitis, peripheral serology, immune markers, cytokine